2016
DOI: 10.3389/fcell.2016.00125
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Communication between Pathogens and Immune Cells via Bacterial Membrane Vesicles

Abstract: The production of extracellular vesicles is a universal mechanism for intercellular communication that is conserved across kingdoms. Prokaryotes secrete 50–250 nm membrane vesicles (MVs) in a manner that is regulated by environmental stress and is thought to promote survival. Since many types of host-derived stress are encountered during infection, this implies an important role for MV secretion in bacterial pathogenesis. Accordingly, MVs produced by gram-positive and gram-negative pathogens contain toxins, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 57 publications
(82 reference statements)
2
33
0
3
Order By: Relevance
“…2017), allowing cells to secrete and share with other cells lipids, hydrophobic, leaderless or denatured proteins, or hydrophobic signaling molecules (for recent reviews, see Jurkoshek et al. 2016; Penfornis et al. 2016; Tkach and Théry 2016; Domingues and Nielsen 2017; Kouwaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…2017), allowing cells to secrete and share with other cells lipids, hydrophobic, leaderless or denatured proteins, or hydrophobic signaling molecules (for recent reviews, see Jurkoshek et al. 2016; Penfornis et al. 2016; Tkach and Théry 2016; Domingues and Nielsen 2017; Kouwaki et al.…”
Section: Introductionmentioning
confidence: 99%
“… 2017 ), protein antigens to dendritic cells (Jurkoshek et al. 2016 ) and mycobactin-iron to neighboring bacteria (Prados-Rosales et al. 2014c ), but the mechanisms involved in MEV interactions with host or bacterial cells are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that MEVs containing immunodominant antigenic proteins could transfer antigens to dendritic cells for presentation to T-cells (Jurkoshek et al. 2016 ), suggesting that MEVs participate in immune stimulation. It has been demonstrated that EVs released by M. tuberculosis -infected macrophages constitute a mixture of macrophage-derived exosomes and MEVs (Athman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse bone marrow-derived macrophages (BMM) stimulated with purified BCG BMV produce IL-1β, IL-6, IL-12, TNF, CXCL1 in a TLR2-dependent way as well as MIP-1α and IL-10, independently of TLR2 ( 51 , 52 ). In addition, BMV are capable to deliver antigens to dendritic cells leading to T cells stimulation ( 61 ). In contrast, Mtb BMV were described as inhibiting CD4 + T cells activation in vitro ( 62 ) through the direct delivery of LAM, which has been previously shown to repress TCR signaling ( 63 ).…”
Section: In Vivo and In Vitro Immunomodulmentioning
confidence: 99%